Desenvolvimento de um sistema de entrega controlada de estímulo olfativo - Lamadrid, Ingrid Gradaschi (2020)
Over the past two centuries, significant demographic changes have occurred accompanied by a rise in average life expectancy, increasing the population over 60 years. As a consequence of this process, there has been an increase in the incidence of aging-related diseases (neurodegenerative diseases), which can affect olfactoryrelated brain parts, leading to a prevalent loss of smell perception in these diseases. The assessment of olfactory capacity is performed in several ways, can be by specific methods, with the aid of neuroimaging techniques or through clinical tests. There are two types of clinical tests, electrophysiological, based on olfactory potentials detected in the brain, which gives this method a high cost of execution and day-to-day unfeasibility, and psychophysicists, which assess olfactory capacity, that is, the olfactory threshold, the discrimination and the identification of odors. However, these methods are carried out manually, which makes the procedure subject to information loss and environmental contamination. In conjunction with these evaluation methods, there are also systems/equipment (olfactometers) that assist in the olfactory evaluation, providing the olfactory stimulus. Given this scenario, this work proposes the development of a controlled delivery system of olfactory stimulus, called olfactometer. The developed system is evaluated according to three parameters, they are: adequate air flow for sufficient exposure to the olfactory stimulus, reproducible from this stimulus and the system’s temporal response. The parameters of air flow and reproducibility of the olfactory stimulus are analyzed through the processing of digital images, replacing an odorous substance with a coloring substance and spraying it on a white paper, generating the samples that are digitized. The system’s temporal response is measured using an oxygen sensor. To this end, an interface is proposed that, in addition to controlling the olfactometer, still reproducing the test Sniffin’ Sticks, allows the doctor to carry out an evaluation of the olfactory evaluation through a computer. Therefore, a contribution of the present dissertation does not lie in the development of a method and an electronic system that aim to increase or decrease the degree of automation of the delivery procedure controlled by olfactory stimulus and, with that, increase the results indexes and the repeatability capacity. of the process.